How drinking motives mediate associations between sexual orientation and indicators of alcohol use – a study among young Swiss men - Wicki, Matthias; Marmet, Simon; Studer, Joseph; Bloomfield, Kim; Gmel, Gerhard (Frontiers in Psychology, 2025)
BackgroundIndividuals with a minority sexual orientation have consistently been found to face a greater risk of mental health problems and problematic substance use than heterosexual individuals. The present study examined whether differences in alcohol use or alcohol use disorder (AUD) symptoms across the spectrum of sexual orientations could be explained by drinking motives (i.e., enhancement, social, coping and conformity motives).MethodA non-self-selective sample of non-abstinent, young Swiss men (N = 5,139; mean age = 25.4, SD = 1.25) completed a self-reporting questionnaire on sexual orientation (on a five-point attraction scale: heterosexual, mostly-heterosexual, bisexual, mostly-homosexual, homosexual), drinking motives, alcohol use indicators (e.g., heavy episodic drinking, Alcohol Use Disorders Identification Test-Consumption [AUDIT-C]), and AUD symptoms. Structural equation modeling was used to test whether drinking motives mediated the associations between dummy-coded sexual orientation (with heterosexual men as the reference) and alcohol use indicators or AUD symptoms.ResultsMostly-heterosexual men exhibited higher scores on alcohol use indicators than heterosexual men, with almost full mediation through their drinking motives, specifically higher enhancement motives. They also reported more AUD symptoms, partially mediated through drinking motives, with comparable contributions from enhancement and coping motives. Homosexual men, however, displayed similar or lower scores for alcohol use indicators and AUD symptoms than heterosexual men, but these differences were not mediated by drinking motives. Indeed, homosexual men exhibited greater coping motives than heterosexual men. No significant results or discernible patterns emerged for bisexual or mostly-homosexual men.DiscussionThese findings highlight the importance of considering the full spectrum of sexual orientations in healthcare and of broadening the focus on drinking motives beyond coping. Understanding the varied motives for alcohol use across the spectrum of sexual orientations facilitates tailored prevention strategies.